Optimalisasi Penggunaan Media Sosial Sebagai Alat Pemasaran Dalam Digital Marketing - Pratiwi, Nuning Indah; Sudipta, I Nyoman Adi; Satria, Wahyu Indra (LPPM UIKA Bogor, 2024)
Optimize the Use of social media as a Marketing Tool in Digital Marketing The main function of social media is to share content, therefore it is necessary to optimize content. Social Media Optimization is almost the same as optimizing social media content. Success on social media means success in optimizing content. Likewise with marketing that will be built at PT SMART VISA BALI through social media. Educating not only prospective service users, but also existing employees. The methods used include direct mentoring, direct mentoring itself, which is a method in which a trainer or mentor is actively involved in the learning or training process by working with participants in real situations or in relevant environments. This assistance can take the form of mentoring, hands-on practice, or joint work situations. The goal is to enable trainees to learn by being directly involved in tasks or situations appropriate to their area of learning. Some of the problems encountered include; lack of utilization of social media features such as Instagram, Facebook, and line. PT Smart Visa is very good at having this social media, but it's a shame if it's not utilized optimally. Social media is made less representative of the services offered. Next is the lack of knowledge related to determining keywords or keywords, the keywords themselves can affect brand/service exposure in the community but again due to a lack of knowledge related to these keywords, the application of social media is not optimal. Based on the research that has been done, it can be concluded that: Optimizing social media has a big impact on companies, apart from being a Digital Marketing marketing medium, through optimizing social media we can also obtain information and make companies sensitive to existing information. development of digital technology. So that PT Smart Visa Bali is not left behind in this digital era if the optimization of social media is further improved.